(untitled) (Research, Society and Development, 2023)
The objective of this work was to evaluate the approach of contents referring to native and exotic plant species in Brazil in Science and Biology textbooks. Ten Science (7th year of Elementary School) and Biology (2nd year of High School) textbooks, recommended by the National Textbook Plan (PNLD), were analyzed. Six categories of content evaluation were established in relation to the approach of subjects considered important for understanding the importance of native species and the damage that exotic species cause to the environment in which they are inserted – concept and importance of native species; concept and impacts offered by exotic species; exhibition through images of native and exotic species; emphasis on species native to Brazil; emphasis on native species at risk of extinction; and tips for handling and preserving native species. Of the total number of books analyzed, only three covered the research categories, highlighting three of the six categories. It was observed that the categories that were most covered by the books were: highlighting the native species of Brazil (10 books) and tips for the management and preservation of the native species of Brazil (4 books). It is concluded that textbooks need to improve the way of approaching the contents, expanding the discussions on environmental preservation in Science and Biology books and that teachers should more carefully evaluate the books that will be used in schools, seeking works that best portray the current and local scenario.